Efektivitas Ekstrak Bawang Putih (Allium sativum l) Terhadap Uji Eber dan Organoleptik pada Pengawetan Daging Kambing (Capra aegagrus hircus) - Sigit, Miarsono; Dawa, Leonardony Djira; Nussa, Olan Rahayu Puji Astuti; Rahmawat, Indra (VITEK : Bidang Kedokteran Hewan, 2021)
This study used two kinds of examinations, namely eber and organoleptic on peanut goat meat (Capra aegagrus hircus) using garlic extract (Allium Sativum L). This study is an experimental study using a completely randomized design (CRD) with a sampling technique with four treatments and six replications for each treatment P0 (without treatment), P1 (20%), P2 (40%) and P3 ( 60%). Goat meat samples were taken from the Pucang market in Surabaya. When taken at 6 am, the goat meat that was taken weighed 100 grams. Samples were taken using sterilized glass jars and put in a cool box and brought to the laboratory by soaking for 2 hours then After 2 hours the goat meat was taken, drained and put in a plastic container, tied with rubber, covered with aluminum foil and allowed to stand at room temperature for 48 hours. After 48 hours the goat meat was taken and continued with the Eber test and organoleptic tests. Goat meat samples were assessed by 20 panelists. Each treatment was observed on the organoleptic test and the eber test. The results that have been obtained are then analyzed using the One Way ANOVA test. The results showed that there was an effect of the effectiveness of garlic extract (Allium sativum L) on mutton beans (Capra aegagrus hircus) and the results for organoleptic tests (color, texture, aroma and taste) were higher at a concentration of 60%. And for the Eber test, the results showed that there was no effect of garlic extract on peanut goat meat.